Genetic and physical interactions reveal overlapping and distinct contributions to meiotic double-strand break formation in C. elegans - Raices, Marilina; Balmir, Fabiola; Silva, Nicola; Li, Wei; Grundy, McKenzie K; Hoffman, Dane K; Altendorfer, Elisabeth; Camacho, Carlos Jaime; Bernstein, Kara A; Colaiácovo, Monica P; Yanowitz, Judith (bioRxiv, 2024)
Double-strand breaks (DSBs) are the most deleterious lesions experienced by our genome. Yet, DSBs are intentionally induced during gamete formation to promote the exchange of genetic material between homologous chromosomes. While the conserved topoisomerase-like enzyme Spo11 catalyzes DSBs, additional regulatory proteins-referred to as "Spo11 accessory factors"- regulate the number, timing, and placement of DSBs during early meiotic prophase ensuring that SPO11 does not wreak havoc on the genome. Despite the importance of the accessory factors, they are poorly conserved at the sequence level suggesting that these factors may adopt unique functions in different species. In this work, we present a detailed analysis of the genetic and physical interactions between the DSB factors in the nematode Caenorhabditis elegans providing new insights into conserved and novel functions of these proteins. This work shows that HIM-5 is the determinant of X-chromosome-specific crossovers and that its retention in the nucleus is dependent on DSB-1, the sole accessory factor that interacts with SPO-11. We further provide evidence that HIM-5 coordinates the actions of the different accessory factors sub-groups, providing insights into how components on the DNA loops may interact with the chromosome axis.
Keywords: Crossover; C. elegans; double-strand break; SPO11; meiosis